2006
DOI: 10.1007/s00109-006-0090-0
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II stimulates apoptosis via TGF-β1 signaling in ventricular cardiomyocytes of rat

Abstract: Elevations in angiotensin II (AngII) and transforming growth factor (TGF-beta1) levels are often found under conditions leading to progression of heart failure. From several studies, it is evident that AngII enhances TGF-beta1 expression via activator protein 1 (AP-1) activation, and that this pathway is involved in hypertrophic growth of the heart muscle and in the development of cardiac fibrosis. We now continued characterization of the signaling pathway stimulated by AngII in ventricular cardiomyocytes of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 44 publications
3
40
0
Order By: Relevance
“…The Akt pro- The results of our study demonstrated that Ang II caused cardiomyocyte apoptosis; this finding is consistent with that of previous studies and shows that Ang II acts as an efficient inducer of apoptosis in adult and neonatal cardiomyo cytes [5,6] . A statistically significant reduction of TUNEL-positive cardiomyocytes was observed when tanshinone IIA was added to Ang-II treated cells.…”
Section: Role Of Akt In the Protective Effect Of Tanshinone Iia On Ansupporting
confidence: 93%
See 1 more Smart Citation
“…The Akt pro- The results of our study demonstrated that Ang II caused cardiomyocyte apoptosis; this finding is consistent with that of previous studies and shows that Ang II acts as an efficient inducer of apoptosis in adult and neonatal cardiomyo cytes [5,6] . A statistically significant reduction of TUNEL-positive cardiomyocytes was observed when tanshinone IIA was added to Ang-II treated cells.…”
Section: Role Of Akt In the Protective Effect Of Tanshinone Iia On Ansupporting
confidence: 93%
“…Pharmacological blockade of the renin-angiotensin system is beneficial in patients with heart failure [4] . Experiments using cultured cardiomyocytes have demonstrated that apoptosis can be stimulated in vitro by angiotensin II (Ang II) [5,6] . Ang II induces cardiomyocyte apoptosis, which contributes to heart failure possibly through enhanced ROS production [6] .…”
Section: Introductionmentioning
confidence: 99%
“…In the cardiovascular system, Angiotensin II (Ang II) promotes fibrosis by its hemodynamic and cellular effects, such as the modulation of TGFb signaling (Dzau, 2001;Schultz et al, 2002;Schroder et al, 2006;Gao et al, 2009;Leask, 2010) and the extracellular matrix turnover, through the major class of proteolitic enzymes (Campos et al, 2003;Castoldi et al, 2003Castoldi et al, , 2007Takenaka et al, 2006). Ang II has two main receptors, the Ang II type 1 receptors (AT1) and the Ang II type 2 receptors (AT2) (Timmermans et al, 1993).…”
mentioning
confidence: 99%
“…Its increased expression is followed by increased collagen deposition in irradiated tissue (Krüse et al 2001, Boerma et al 2002, Wynn 2008, Ferreira-Machado et al 2010. TGF-β1 can also be the primary mediator for apoptosis (Schröder et al 2006), but this relationship is unclear in the irradiated heart. Animals or patients, studies have demonstrated increased apoptosis pathway, evidenced particularly by the presence of cleaved-caspase-3, especially in the following heart diseases: ischemic cardiomyopathy, dilated cardiomyopathy, myocardial infarction, myocarditis, and arrhythmias (Condorelli et al 1999, Feuerstein and Young 2000, Philipp et al 2004, Kunapuli et al 2006, Ferrari et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Growth stimulation initially occurs as a compensatory effort to meet chronically altered hemodynamic demands on the failing myocardium and is mediated by systemic and/or local up-regulation of mediators of adrenergic or rennin-angiotensin axes (Goldspink et al 2003, Schlüter and Wenzel 2008, Whelan et al 2010. Similarly, certain cytokines, like TGF-β1 can induce growth as well as apoptosis (Schröder et al 2006). The induction of apoptosis as a form of cell death distinct from necrosis is associated with activation of aspartate-specifc cysteine proteases such as caspase-3 (Goldspink et al 2003).…”
Section: Introductionmentioning
confidence: 99%